Factors Associated With The Level Of Entrepreneurial Performance Of Graduate Entrepreneurs - Ahmad Zaid, Rosni Jameeah (1994)

(untitled)
This thesis on the graduate entrepreneurs of the Special Graduate Programme ( SGP ) for tax agent saimed to determine the factors associated with the level of entrepreneurial performance of graduate entrepreneurs.A total of 78 graduate entrepreneurs from the state of Selangor and Wilayah Persekutuan were studied.These graduate entrepreneurs were heads of firms which have been operating for at leas t two years.Specifically the study sought to determine the relations hips between the entrepreneurial education and the entrepreneurial development with the level of performance of the graduate entrepreneurs. Frequencies,means and percentages were used to interpret the entrepreneurs ' personal profile, business pro file and the